Diet composition of common carp (Cyprinus carpio Linnaeus, 1758) occurring from sub-tropical river Ganga, Prayagraj, India: Feeding behavior of C. carpio in Ganga - Das, Shyamal Chandra Shukla; Jaiswar, A.K.; Joshi, K. D.; Chakraborty, S. K.; Panda, Debabrata; Alam, Absar; Bhakta, Dibakar; Das, Pronob; Yadav, A. K. (Journal of the Inland Fisheries Society of India, 2023)
The current study is based on gut content analysis of 293 specimens of common carp (Cyprinus carpio) ranging from 90-689 mm in total length. The fish were collected randomly from Teliyarganj and Daraganj fish landing sites, located in the middle stretch of river Ganga River at Prayagraj, India, at monthly intervals from September 2016 to August 2017. The results indicated that C. carpio is predominantly a detri- omnivorous species and mainly feeds on detritus (72.78%), followed by molluscs (11.50%), phytoplankton (6.29%), zooplankton (5.11%), insects (1.63%), macrophytes (2%), and annelids (0.68%). High feeding intensity was observed during the summer and the early winter seasons, while low feeding was observed during the late winter. Ontogenetic dietary changes were noticed with monthly (seasonal) variations as well as in different length groups. The monthly mean gastro-somatic index (GaSI) values of males and females were observed to be low in February at 2.63±0.26, and 2.59±0.22, respectively, while the highest values were observed in May, 5.25±0.38 and 4.97±0.65, for males and females, respectively. The relative length of gut (RLG) values ranged from 1.48±0.10 to 2.36±0.18 for males and 1.46±0.11 to 2.0±0.18 for females. The mean GaSI and RLG values of both sexes varied significantly (p<0.05) over the months. The present findings obtained from this study would be helpful for the successful management of this species in the riverine system.